“Near Ground” Vertical Vorticity in Supercell Thunderstorm Models - Rotunno, Richard; Markowski, Paul M.; Bryan, George H. (Journal of the atmospheric sciences, 2017)
Numerical models of supercell thunderstorms produce near-ground rotation about a vertical axis (i.e., vertical vorticity) after the development of rain-cooled outflows and downdrafts. The physical processes involved in the production of near-ground vertical vorticity in simulated supercells have been a subject of discussion in the literature for over 30 years. One cause for this lengthy discussion is the difficulty in applying the principles of inviscid vorticity dynamics in a continuous fluid to the viscous evolution of discrete Eulerian simulations. The present paper reports on a Lagrangian analysis of near-ground vorticity from an idealized-supercell simulation with enhanced vertical resolution near the lower surface. The parcel that enters the low-level maximum of vertical vorticity has a history of descent during which its horizontal vorticity is considerably enhanced. In its final approach to this region, the parcel’s enhanced horizontal vorticity is tilted to produce vertical vorticity, which is then amplified through vertical stretching as the parcel rises. A simplified theoretical model is developed that exhibits these same features. The principal conclusion is that vertical vorticity at the parcel’s nadir (its lowest point), although helpful, does not need to be positive for rapid near-surface amplification of vertical vorticity.